Composite materials and material engineering. II : selected, peer reviewed papers from the 3rd International Conference on Composite Materials and Material Engineering (ICCMME2018), January 26-28, 2018, Singapore - Zhu, Xiao Hong (Trans Tech Publications Limited, 2018)
The 3rd International Conference on Composite Materials and Material Engineering (ICCMME2018) was held in Singapore on January 26-28, 2018. Papers, published on the results of this conference, cover some aspects of the recent research and development in the area of polymers, composites, functional materials and special alloys, building materials and technologies of materials processing. Polymers, Composites, Alloys, Ceramics, Nanomaterials, Functional Materials, Processing Technology, Building Materials Materials Science.